Coconut Shell Waste Treatment Technology for A Sustainable Waste Utilization: A Case Study of the SMEs in Bohol Village, Indonesia - Rizal, Wahyu Anggo; Suryani, Ria; Maryana, Roni; Prasetyo, Dwi Joko; Pratiwi, Diah; Ratnawati, Yuli Ary; Ariani, Dini; Suwanto, Andri (UI Scholars Hub, 2022)
This project focused on the introduction of liquid smoke and bio briquette manufacturing technology to small and medium enterprises (SMEs) located in Bohol Village, Gunungkidul, Indonesia through technology transfer, training, and mentoring. These SMEs are engaged in the food business with the main product jenang ketan, a traditional food from Gunungkidul, especially in Rongkop District, and very popular among communities around and outside Gunungkidul. The traditional preparation of jenang ketan produces several by-products in the form of waste, which is dominated by coconut shell biomass. The project’s technology transfer was carried out through the procurement of a series of pyrolysis reactors, distillation reactors, grinder machines, mixer machines, and briquette press machines for SMEs. Afterwards, the training was performed through teaching and practice of SMEs with a focus on the pyrolysis process, bio-briquette process, distillation, application of liquid smoke and bio-briquette, and marketing techniques. The activity was conducted within a period of one-year; continuous mentoring was carried out for the SMEs through consultation and direct field evaluation. The result of the project revealed an increase in the knowledge of SME personnel in the processing of coconut shells waste to produce liquid smoke and bio-briquette and the capability of SMEs to produce their own liquid smoke and briquette.